Kontroversi Pencabutan Gigi Permanen Muda Pada Perawatan Ortodonsi - Alifuddin Zuhri; Adam Malik Hamudeng; Ardiansyah S. Pawinru (DiscoverSys Inc., 2007)
Permanent tooth extraction in the children and teenager patients, eitherdue to of tooth decay or esthetical orthodontic reason, will have directeffect to central nervous system and disturb the growth anddevelopment process of the children and teenager patient's tooth andjaw and indirect effect in closing of the opportunities of the patiententering some vital job, like army cadet, pilot and stewardess. Ifextraction is based on orthodontic analyses, there are at least 3 : newproblems will arise, namely neurological effect to central nervoussystem, non-optimal occlusion and disturbance on growth anddevelopment process of the patient tooth and jaw, and there is a legalproblem if some day the patient realize that they lost their vitalopportunity due to of irrational intervention to their tooth. Are theworldwide orthodontists theory will safe us from the claim of IndonesianAct No. 23 Year 2002 and Act No. 29 Year 2005? This paper aim torealize dentist that the old orthodontic theory is not always true at alltime; society, either physically or economically lost some intact tooth,due to of unrevised theory; and to warrant the dentist that permanenttooth extraction is an illegal intervention in conjunction with the Acts,because dentists do not protect the existence of the intact tooth. Thereare some preventive measures alternative to safe the children andteenager intact tooth, started from oral health for all, optimalization ofspace-maintaining and regaining concept, i and better understandingabout orthodontic myofunctional theory.